2010
DOI: 10.1016/j.memsci.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The salt-, pH- and oxidant-responsive pervaporation behaviors of weak polyelectrolyte multilayer membranes

Abstract: a b s t r a c tThe layer-by-layer (LbL) assembled polyelectrolyte multilayer has recently been recognized as a new class of promising membrane material for various separation uses. However, there is a lack of understanding about the influences of separation mixtures on the adsorbed polyelectrolytes. Therefore, clear understanding on it would be very important for the design and application of a type of new functional composite membrane. In this paper, the multilayer of weak polyelectrolytes polyethyleneimine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 39 publications
0
28
1
Order By: Relevance
“…For example, we have recently reported that the post-treatments of the weak polyelectrolyte multilayer membranes with salt, acid, and alkali offer much opportunity for the formation of loose structure and big defects on multilayers, which would in turn lead to the deterioration of membrane performance. 28 To improve the stability, a metal-ligand-coordinated multilayer membrane has been recently developed for separation applications in our laboratory. 29 In contrast, covalent bonding may yield much more stable structures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, we have recently reported that the post-treatments of the weak polyelectrolyte multilayer membranes with salt, acid, and alkali offer much opportunity for the formation of loose structure and big defects on multilayers, which would in turn lead to the deterioration of membrane performance. 28 To improve the stability, a metal-ligand-coordinated multilayer membrane has been recently developed for separation applications in our laboratory. 29 In contrast, covalent bonding may yield much more stable structures.…”
Section: Introductionmentioning
confidence: 99%
“…This type of module may offer advantages such as easy formation of ultrathin selective layer, easy protection of the separation layer, good distribution of feed solution, and low-transport resistance on the permeate side. 20,21,28,29 Recently, a pilot-scale inner skin hollow fiber pervaporation module with a length of 1 m was successfully produced in our laboratory. 21 It suggested that the inner skin hollow fiber pervaporation membranes have great potential for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because some of the PEI/PAA may have swelled and partly peeled off, due to the b-CD-IL assembly process. [30][31][32] It was clear that although the b-CD-IL can be assembled on to the PEI/PAA due to the electrostatic adsorption force, the b-CD-IL will, to Figure 7. UV-vis spectra of (PAA/IL) n films with n 5 1-6 on quartz substrates.…”
Section: Morphologies Of B-cd-il/paa Membranesmentioning
confidence: 99%